2006
DOI: 10.1152/ajprenal.00387.2005
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II mediates downregulation of aquaporin water channels and key renal sodium transporters in response to urinary tract obstruction

Abstract: The renin-angiotensin system is well known to be involved in the pathophysiological changes in renal function after obstruction of the ureter. Previously, we demonstrated that bilateral ureteral obstruction (BUO) is associated with dramatic changes in the expression of both renal sodium transporters and aquaporin water channels (AQPs). We now examined the effects of the AT(1)-receptor antagonist candesartan on the dysregulation of AQPs and key renal sodium transporters in rats subjected to 24-h BUO and followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
53
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 58 publications
8
53
0
Order By: Relevance
“…Given the knowledge that the RAA system typically acts to preserve sodium and water, we might be left to conclude that in the UUO model, the resistance to AVP and subsequent diuresis must represent a powerful signal that overrides the pressor effect of local increases in RAA system activity. However, it is very interesting to note, that in bilateral ureteric obstruction in rats, angiotensin II actually mediates downregulation of certain aquaporin water channels and key renal Na + transporters [28]. This is an area which requires further investigation in a UUO model.…”
Section: Discussionmentioning
confidence: 98%
“…Given the knowledge that the RAA system typically acts to preserve sodium and water, we might be left to conclude that in the UUO model, the resistance to AVP and subsequent diuresis must represent a powerful signal that overrides the pressor effect of local increases in RAA system activity. However, it is very interesting to note, that in bilateral ureteric obstruction in rats, angiotensin II actually mediates downregulation of certain aquaporin water channels and key renal Na + transporters [28]. This is an area which requires further investigation in a UUO model.…”
Section: Discussionmentioning
confidence: 98%
“…ANG II is a potent vasoconstrictor and sodium-retaining hormone that plays a vital role in the regulation of blood pressure and is believed to contribute to the progression of cardiovascular and renal disease (24, 37). The role of ANG II in the regulation of NCC trafficking is not known; however, multiple studies have demonstrated the involvement of ANG II in the regulation of abundance of major renal sodium transporters such as ENaC, NKCC2, NHE3, and NCC (2,11,16). A role of ANG II in trafficking of the proximal tubule sodium transporter NHE3 has been demonstrated in a recent study from the McDonough laboratory: acute infusion of the angiotensin-converting enzyme (ACE) inhibitor captopril provoked the redistribution of NHE3 to the base of the proximal tubule apical microvilli accompanied by increased proximal tubule flow and diuresis (18).…”
mentioning
confidence: 99%
“…Previous studies showed that at least part of the COX-2 induction is attributable to ANG II since ANG II receptor type 1A (AT1) blockade significantly reduced COX-2 abundance in the postobstructed kidney (21). Furthermore, AT1 receptor blockade attenuates downregulation of V2R and the vasopressin-regulated transport proteins pS256-AQP2, AQP2, and NKCC2 48 h after release of 24-h BUO (20,21).…”
mentioning
confidence: 98%
“…Importantly, the vasopressin type 2 receptor (V2R) and vasopressin-regulated transport proteins are downregulated, causing vasopressinresistant polyuria (20,51,55). A number of hormone/signaling systems contribute to postobstructive kidney disease, including the prostanoid system (13,26,32,36) and the renin-angiotensin-system (RAS) (21,40,56).The most abundant prostaglandin in the kidney, prostaglandin E 2 (PGE 2 ), is involved in the regulation of kidney water and salt handling. In the medullary thick ascending limb (TAL), PGE 2 acutely blunts vasopressin-stimulated NaCl transport and cAMP generation (9, 46, 49) and the long-term effect of PGE 2 is downregulation of the vasopressin-regulated Na-K-2Cl cotransporter (NKCC2) (12).…”
mentioning
confidence: 99%
See 1 more Smart Citation